2015
DOI: 10.5849/jof.14-066
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Wildfire Recency and Frequency on an Appalachian Oak Forest

Abstract: Cabwaylingo State Forest in southern West Virginia has experienced numerous anthropogenic wildfires over the past 36 years. In this case study, we assessed the relationship between fire frequency and recency and stand composition and structure, with emphasis on oak and its competitors. Frequent and recent fire was significantly correlated with reduced red maple overstory stem density and basal area. Overstory oak density did not significantly vary with either fire frequency or recency. Total overstory basal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For many years, forest managers and silviculturists have attempted to utilize prescribed fire to avert potentially negative mesophication impacts in long-term non-burned forests residing in historically frequent fire landscapes [7,44,45]. In many cases dormant season prescribed fires as a singular treatment have produced less than desired results to reduce mesophytic hardwood competition and increase oak regeneration [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, forest managers and silviculturists have attempted to utilize prescribed fire to avert potentially negative mesophication impacts in long-term non-burned forests residing in historically frequent fire landscapes [7,44,45]. In many cases dormant season prescribed fires as a singular treatment have produced less than desired results to reduce mesophytic hardwood competition and increase oak regeneration [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…, Thomas‐Van Gundy et al. ). However, we found that subsequent fires continually reduced abundance of red maple in the large seedling and sapling layers, and by Y13, most of the larger red maple stems had been eliminated; the thin bark of red maple makes it especially sensitive to heat damage and its sprouting capacity was reduced with multiple fires (Hare , Harmon , Hammond et al.…”
Section: Discussionmentioning
confidence: 99%
“…The "super-generalist" red maple (Abrams 1998) is often the most intense competitor to oakhickory regeneration in many areas of the Central Hardwoods, and sprouts vigorously following a harvest or a single fire (Albrecht and McCarthy 2006, Iverson et al 2008, Schuler et al 2013, Thomas-Van Gundy et al 2015. However, we found that subsequent fires continually reduced abundance of red maple in the large seedling and sapling layers, and by Y13, most of the larger red maple stems had been eliminated; the thin bark of red maple makes it especially sensitive to heat damage and its sprouting capacity was reduced with multiple fires (Hare 1965, Harmon 1984, Hammond et al 2015.…”
Section: Dynamics Of Competing Vegetationmentioning
confidence: 99%
“…Methods to do so include the use of fire or midstory removal. For instance, one study found that fire increased the number of tall oak stems per acre over no fire [21]. Another study found that spring burns and winter burns resulted in increased oak reproduction height 11 years after a single fire in shelterwood stands [22].…”
Section: Competition Controlmentioning
confidence: 99%